Tailoring interlayer spacing of Ti3C2Tx MXene with organic acid doped polyaniline and polypyrrole for more stable supercapacitors - Lima, João V.M. [UNESP]; Lemos, Hugo G. [UNESP]; Silva, Rafael A. [UNESP]; Rossato, Jéssica H.H. [UNESP]; Boratto, Miguel H. [UNESP]; Graeff, Carlos F.O. [UNESP] (Elsevier, 2024)
Polyaniline (PANI) and polypyrrole (PPy) are promising for use as spacers materials to prevent re-stacking of MXene layers and to increase their electrochemical properties. However, these conducting polymers (CPs) may undergo hydrolysis during long charge-discharge cycles. The use of organic acids to dope CPs may lead to better polymer cyclic stability. However, PANI and PPy used as spacers in MXene are mainly doped with inorganic acids. Herein, we applied dodecylbenzenesulfonic acid (DBSA) doped PANI and PPy as effective spacers and additional pseudocapacitance agents for Ti3C2Tx MXene. Taking advantage of the favored dispersibility of the functional inks in water, we easily prepared the electrodes by drop casting. X-ray diffractograms confirmed that the CPs are effectively allocated among MXenes sheets. Spectroscopic analyses showed that the functional groups of Ti3C2Tx may work as effective dopants for PANI and PPy. The enhanced interlayer spacing of MXenes and increased high conductivity of CPs boosted capacitance from 175 F g−1 (Ti3C2Tx) to 255 F g−1 and 270 F g−1 at 1 A g−1 after addition of 10 wt% of PANI and PPy, respectively, at a three-electrode setup. The Dunn’s and Trasatti’s methods showed greater pseudocapacitive contribution after addition of PPy and greater double layer capacitance contribution after addition of PANI. Similarly, symmetric solid-state SCs exhibited enhancement of 72 % in specific capacitance for Ti3C2Tx/PANI and 208 % for Ti3C2Tx/PPy, when compared to pristine Ti3C2Tx. SCs based on Ti3C2Tx/CPs also yielded outstanding capacitance retentions (>98 %) after 5000 cycles against only 88 % of the Ti3C2Tx pristine device. These results indicate that the organic doped-CPs modulated interlayer spacing of MXene sheets, preventing their re-stacking during the charge and discharge cycles. Finally, the aqueous Ti3C2Tx/CPs based inks is an eco-friendly and low-cost alternative to fabricate SCs with enhanced capacitance and stability.